A SIMPLE AND RAPID METHOD FOR THE SIMULTANEOUS DETERMINATION OF CALCIUM AND MAGNESIUM FROM THE SAME SAMPLE OF BLOOD SERUM - Kovács, G. S. (1960)
A simple and rapid procedure has been developed for the complexometric titration of serum calcium and magnesium using “plasmocorinth B” as indicator. Both determinations can be carried out from the same 0.5 ml. sample. The method is in good agreement with the established calcium and magnesium methods.